Marketing and Economy Interlinkages: View of Rural India - Majumder, Indrani (Prabandhan: Indian Journal of Management, 2009)
Marketing activities are the only way of quantification of the flow of physical elements within an economy. It is the one and only one basis of value addition within an economy and thus promotes the economic growth. The emergence of market and the marketing activities can take the lead of comparative advantage and can make possible the development of an economy in isolation and overall world development in integration. This paper tries to explore this interrelationship between the marketing activities of the organizations and the economic magnification of a nation in the light of the rural marketing activities of the organizations within Indian geographical territory. The study, on the one side, reveals the pace of economic progress of the rural counterpart of India after independence and simultaneously gives a focus on the marketing performance of some business organizations (from FMCG to consumer durables and services). Ultimately in the present study an attempt has been made to find out the direction of their relationship. The study has tried to explore whether the marketing activities of the organization really empowered the rural independent Indian or not. The study ultimately suggests that up-to-the-mark marketing activities are the prerequisite for a high level of economic activity. It suggests that the customer is the only foundation of any business unit; it is the customer that alone posses the right to create employment; and considering the society’s norms the organizations have to take the responsibility to make the people capable so that they can supply wealth-producing resources to the organizations and at the same time can give the return to those units.